2010
DOI: 10.1098/rsta.2010.0125
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule precursor-based approaches to cobalt sulphide nanostructures

Abstract: Cobalt complexes of 1,1,5,5-tetramethyl-2,4-dithiobiuret, [Co{N(SCNMe 2 ) 2 } 3 ] (1), and 1,1,5,5-tetraisopropyl-2-thiobiuret, [Co{N(SOCN i Pr 2 ) 2 } 2 ] (2), have been synthesized and characterized. Both complexes were used as single-molecule precursors for the preparation of cobalt sulphide nanoparticles by thermolysis in hexadecylamine, octadecylamine or oleylamine. The powder X-ray diffraction pattern of as-prepared nanoparticles showed the hexagonal phase of Co 1−x S from complex 1 and mixtures of cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Various single source precursors have been investigated including metal complexes of dialkyldithiocarbamates, alkyl xanthates, and dimorpholino dithioacetylacetonates . We have recently demonstrated that thio- and dithio-biuret metal complexes can be used as single source precursors for the preparation of various metal sulfide thin films and nanoparticles . In continuing this work, we report the synthesis of Zn and Cd complexes of 1,1,5,5-tetraalkyl-2-4-dithiobiurets (R = methyl or ethyl) and 1,1,5,5-tetraalkyl-2-thiobiurets (R = isopropyl) and their use as single molecular precursors for deposition of ZnS, CdS, and Zn x Cd 1− x S thin films by AACVD.…”
Section: Introductionmentioning
confidence: 99%
“…Various single source precursors have been investigated including metal complexes of dialkyldithiocarbamates, alkyl xanthates, and dimorpholino dithioacetylacetonates . We have recently demonstrated that thio- and dithio-biuret metal complexes can be used as single source precursors for the preparation of various metal sulfide thin films and nanoparticles . In continuing this work, we report the synthesis of Zn and Cd complexes of 1,1,5,5-tetraalkyl-2-4-dithiobiurets (R = methyl or ethyl) and 1,1,5,5-tetraalkyl-2-thiobiurets (R = isopropyl) and their use as single molecular precursors for deposition of ZnS, CdS, and Zn x Cd 1− x S thin films by AACVD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of cobalt sulfide in dye degradation and adsorption has not been explored much. Additionally, it is low-cost material and has different stoichiometric and nonstoichiometric phases of cobalt sulfides such as Co 4 S 3 , Co 9 S 8 , CoS, Co 3 S 4 , Co 2 S 3 , Co 1– x S, and CoS 2 . Therefore, we chose cobalt sulfide as the material of choice for photocatalytic and adsorption studies. The band gap, phase, and morphology of this material can be tuned synthetically by decreasing the size to nano regime as per need that is suitable for the removal of organic dyes via visible-light photocatalysis and adsorption. , In this study, we developed a low-temperature wet-chemical green route for the synthesis of cobalt sulfide NS with different phase and morphology (Scheme ) and subsequently used it for photocatalysis and adsorption studies.…”
Section: Introductionmentioning
confidence: 99%
“…The higher intensity of (001) peak suggests that brucite-like β-Co(OH) 2 prefers the growth direction along the (001) crystal plane, [ 31 ] consistent with the FFT and high resolution TEM (HRTEM) results. In addition, the peaks corresponding to CoS x (311) are observed at 29.7° (labeled as ♣), [ 32 ] those corresponding to CoS nanoparticle (100) and (101) are observed at 33.9° and 36.2°, respectively (labeled as ♠). [ 33 ] The accounts for the aMoS 2+ x (labeled as * ) and nickel foam (labeled as #) peaks are given in Figure S7 in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%